Constrained Magnetostratigraphic Dating of a Continental Middle Miocene Section in the Arid Central Asia - Verestek, Verena; Appel, Erwin; Voigt, Silke; Frisch, Konstantin (Frontiers in Earth Science, 2018)
The Neogene succession of the Aktau Mountains in the Ili Basin, southeast Kazakhstan, is a terrestrial archive well suited for researching the role of Central Asia in Miocene climate evolution. We present an integrated approach for dating the well-exposed Bastau Formation, based on magnetostratigraphy and constraints from cyclostratigraphy and biostratigraphy. Stepwise demagnetization yielded characteristic remanence directions that are consistent with those expected for the Miocene in Central Asia. The reddish-colored alluvial floodplain deposits and grey lacustrine deposits show partly complex magnetic behavior with magnetite and hematite as the main magnetic carriers, with variable demagnetization behavior and non-dipolar normal and reverse polarity directions. The observed magnetic properties are best explained by depositional variability and magneto-mineralogical alteration effects of both dissolution and neo-formation of magnetite, including significant secondary magnetization. The mean of reverse polarity directions is flatter than the expected Middle Miocene Earth magnetic field, which is an indicator for the existence of inclination shallowing that supports a primary origin. Detailed rock magnetic analyses are used to analyze the nature of the characteristic remanent magnetization and to discriminate primary and secondary remanence directions in order to obtain a reliable magnetostratigraphic result. The proposed age of 15.3 Ma to 13.9 Ma for the Bastau Formation corresponds to the known biostratigraphic setting, matches with typical sedimentation rates of foreland basins in Central Asia, and coincides with spectral analysis of geochemical proxies of that section. The resulting age model serves as a robust framework for paleoclimate reconstruction of Neogene climate dynamics in Central Asia.